Pengaruh Kepercayaan dan Pemanfaatan Media Sosial Terhadap Keputusan Pembelian di Toko Kain Jumputan Din’s Nusantara (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT This study aims to determine the effect of trust and the use of social media on purchasing decisions at  Jumputan Din's Nusantara Store. The analysis was carried out using the quantitative method of the SPSS for windows version 22 program. Based on the results of this study, it can be seen that the variable t test shows that the sig value is 0.596 > 0.05. The results of this study do not prove the truth of hypothesis 1, the trust variable partially has no significant effect on purchasing decisions at the Jumputan Din's Nusantara Fabric Shop. Based on the t test, it shows that the sig value is 0.04 0,05. Hasil penelitian ini tidak membuktikan kebenaran hipotesis 1, variabel kepercayaan secara parsial berpengaruh tidak signifikan terhadap keputusan pembelian di Toko Kain Jumputan Din’s Nusantara. Berdasarkan uji t menunjukkan bahwa nilai sig 0,04